Transformation of education as the most important factor in the development of the economic society of Uzbekistan (Journal of Pedagogical Inventions and Practices, 2023)
Today, in the economic development of Uzbekistan, the processes of transformation and development of the digital economy are considered topical issues. Transformation (lat. transformatio - change, adaptation) is the process of development of the world economy, the ability of society to adapt to new conditions.